a)
[tex]2x + 6y - (3x + 9 + 4y) - xy - (2x + 5y)\\2x + 6y - 3x - 9 - 4y - xy - 2x - 5y\\-xy-3x-3y-9\ ,\ \begin{cases}x = -2\\y = 2\end{cases}\\-(-2)*2-3(-2)-3*2-9=-5[/tex]
b)
[tex]- (3x - 2y) + [-(- 5x + 4y) + 3xy] - (2x - 2y + xy)\\-3x+2y+5x-4y+3xy-2x+2y-xy\\2xy\ ,\ \begin{cases}x =3 \\y = -2\end{cases}\\2*3*(-2)=-12[/tex]
c)
[tex]-xy [ - (7x^2 + 2y -3) - (-2y + 6 - 3x) + (-x)] - (-5x + 9)\\xy[(7x^2 + 2y -3)+(-2y + 6 - 3x)+x]+5x-9\\xy(7x^2 + 2y -3-2y + 6 - 3x+x)+5x-9\\7x^3y + 2xy^2 -3xy-2xy^2 + 6xy - 3x^2y+x^2y+5x-9\\7x^3y-2x^2y+3xy+5x-9\ ,\ \begin{cases}x = -1\\ y = 2\end{cases}\\7(-1)^3*2-2(-1)^2*2+3(-1)*2+5(-1)-9=-14-4-6-5-9=-38[/tex]